Jaran Kepang Papat: From the Indigenous Dancing to the Contemporary Practice in Strengthening the Theological Value of Salvation - Halim Wiryadinata (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2026)
This research aims to show that indigenous dancing expresses religious teaching through its rites and rituals, which must be performed in the community as a way of life in strengthening the value of theology of salvation. Jaran Kepang Papat is the indigenous dance of the Javanese, and it expresses the dogma of prayers for salvation and prosperity through the movement and songs conducted. This intersection uses the sociology of religion method through analytical and logical writing. Therefore, this article argues that the value of the indigenous dancing Jaran Kepang Papat quickens the theological value of salvation through the perspective of Sedulur Papat Kalima Pancer. As a result, this study finds that Jaran Kepang Papat's dancing highlights the theological concept of salvation in Christianity through the forming of behavior and attitude in society. This study concludes that Jaran Kepang Papat's dancing proves that local culture and dogma are mutually reinforced in society.